Engaging student synergy: INFORMS team building / Dr. Hajah Imilia Ibrahim - Ibrahim, Imilia (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
According to tradition, the Information Management Society of UiTM Sarawak organizes an INFORMS Team Building program every semester. The event took place on November 3rd and 4th, 2023, at the UiTMSarawak Jubilee Hall and Student Center. The event was intended to bring together students from the faculty, particularly those in the first through third semesters, to learn about and experience being a student at the School of Information Science and meet others in the same faculty. The two-day event was planned to provide students with various activities, including knowledge sharing, fun and games, and a talent competition. The first day of the event began with a session titled An Evening with YODA (Your Dedicated Academia). This session brought together students and lecturers for a knowledge-sharing session. Students were free to ask any lecturer questions, and the lecturers took advantage of the opportunity to share their experiences as both students and faculty members.